The efficacy and safety of PD-1/PD-L1 inhibitors in patients with recurrent or metastatic nasopharyngeal carcinoma: A systematic review and meta-analysis. (May 2020) - Wang, Bi-Cheng; Cao, Ru-Bo; Fu, Chen; Chen, Wang-Bing; Li, Pin-Dong; Lin, Guo-He; Qian, Xiao-Jun; Li, Yun-Tian; Liu, Quentin
Highlights: In R/M NPC treated with PD-1 inhibitors, the ORR was 27% and the DCR was 63%. The 1-year PFS rates was 25% in the PD-1 inhibitors treatment. The 1-year OS rate was 61% when R/M NPC was treated with anti-PD-1 agents. Abstract: Objectives: There is currently no effective salvage therapeutic modality that improves the survival outcomes of patients with recurrent or metastatic nasopharyngeal carcinoma. However, the programmed cell death protein 1 (PD-1) and its ligand (PD-L1) inhibitors may provide clinical benefit for these advanced patients. Materials and methods: The databases, including PubMed, Web of Science, EMBASE and Cochrane Library, were systematically searched up to Nov 5, 2019. Data of objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS) rate, overall survival (OS) rate, and drug-related adverse events were extracted and pooled meta-analyzed. Results: From 71 search records, eight studies were included in the systematic review, of which three were eligible for final meta-analysis. In recurrent or metastatic nasopharyngeal carcinoma patients treated with anti-PD-1 therapy, the pooled ORR was 27% (95% confidence interval [CI] 19–36%), DCR was 63% (95% CI 50–75%), 6 months PFS rate was 49% (95% CI 40–58%), 1-year PFS rate was 25% (95% CI 19–32%), 1-year OS rate was 61% (95% CI 49–72%). The pooled incidences of any grade and grade ≥ 3 drug-related adverse events were 94% and 20% respectively. Conclusion: We present the aggregate response rates, survival rates and incidences of drug-related adverse events for recurrent or metastatic nasopharyngeal carcinoma patients receiving PD-1/PD-L1 blockage treatment, which could provide useful information for future design of clinical studies. There is a need for more randomized controlled studies with head-to-head comparison of PD-1/PD-L1 inhibitors and traditional chemotherapeutic strategies to enable better recommendations for optimal advanced nasopharyngeal carcinoma treatment.